Shift from chronic to episodic migraine frequency in a long-term phase 3 study of galcanezumab - Diener, Hans-Christoph; Day, Kathleen A.; Lipsius, Sarah; Aurora, Sheena K.; Hindiyeh, Nada A.; Detke, Holland C. (Journal of headache and pain, 2025)
Background Chronic migraine (CM) is a highly disabling form of migraine in which patients have ≥ 15 headache days per month, of which at least 8 have the features of migraine. Galcanezumab is a monoclonal antibody to calcitonin gene-related peptide which is approved for the preventive treatment of migraine. Ability to convert patients from chronic migraine frequency to episodic migraine (EM) frequency is a clinically relevant and desirable outcome when prescribing preventive treatments to patients with CM. Methods Patients aged 18–65 years with an ICHD-3β diagnosis of CM were randomized 2:1:1 to receive monthly injections of placebo ( N = 558), galcanezumab 120 mg with a 240-mg loading dose ( N = 278), or galcanezumab 240 mg ( N = 277) during a 3-month double-blind period of the phase 3 REGAIN trial. Patients could subsequently enter a 9-month open-label extension in which they received galcanezumab 120 mg or 240 mg/month per investigator’s discretion. In this post-hoc analysis, we assessed the percentages of patients who shifted to EM (< 8 migraine headache days or < 15 headache days/month), low frequency EM (LFEM; <8 migraine headache days/month), and very low frequency EM (VLFEM; <4 migraine headache days/month) for at least 3 consecutive months. Double-blind percentage comparisons versus placebo represent modeled estimates from raw rates. Results At baseline, patients had a mean of 19.4 migraine headache days per month (SD = 4.5) and 21.4 headache days per month (SD = 4.1). During the 3-month double-blind treatment period, a greater percentage of galcanezumab-treated patients shifted to EM frequency and maintained it across all 3 months (31.5%) than did placebo-treated patients (19.8%, p < 0.001). Among galcanezumab-treated patients across the entire 12-month trial, 65.1% shifted from CM to EM frequency, with 44.2% shifting to LFEM and 21.5% shifting to VLFEM for ≥ 3 consecutive months. Proportions of patients shifting from CM to EM frequency for ≥ 3 consecutive months and until last patient visit were: 55.0% to EM; 33.4% to LFEM; 13.9% to VLFEM. Conclusion These results suggest that galcanezumab helped a majority of patients convert from chronic to episodic migraine frequency over the course of this 12-month study. Trial registration Clinicaltrials.gov NCT02614261, first registered November 25, 2015.